Eksplorasi Preferensi Media Pembelajaran Fikih Berbasis Daya Ingat Siswa Pada Mata Pelajaran Fikih Kelas VIII Di MTS Manbail Futuh - Riswanda Arneta Pratiwi; Alfi Manzilatir Rohmah (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study aims to determine the appropriate choice of Fiqh learning media for eighth-grade students at MTs Manbail Futuh Jenu. The background of this study is the low ability of students to remember Fiqh material due to the dominant use of lectures and textbooks. The method used in this study was descriptive qualitative, with data collected through observation, in-depth interviews, and documentation. The research findings indicate that the majority of students prefer audio-visual, visual, and interactive learning media such as videos, animations, illustrative images, flashcards, and educational games. The use of these media facilitates students' understanding and retention of practical Fiqh material, such as ablution, tayammum, and prayer. Conversely, the use of lectures without engaging media quickly causes students to become bored and struggle to retain the material. This study concludes that selecting learning media that aligns with students' preferences can improve their memory and comprehension of Fiqh material.